2016
DOI: 10.1007/s10753-016-0358-7
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Linolenic Acid Suppresses NF-κΒ Signaling via CD36 in the Lipopolysaccharide-Induced Inflammatory Response in Primary Goat Mammary Gland Epithelial Cells

Abstract: Gamma-linolenic acid (GLA) and linoleic acid (LA), which are both n-6 unsaturated fatty acids, play vital roles in lipopolysaccharide (LPS)-induced inflammation. The multi-functional protein scavenger receptor CD36 has also been shown to participate in inflammation. However, the molecular mechanisms underlying the interactions between CD36 and GLA or LA in LPS-induced inflammation remain unclear. We used small interfering RNA and adenoviral systems to manipulate CD36 expression in primary goat mammary gland ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Hence, among the lipid components of Spirulina lipids, GLA bonded to GLs may possibly be the main contributor reducing the excess fat accumulation in the liver induced by the HFHSD. Furthermore, several studies have reported that GLA exerts a potent anti-inflammatory activity both in vitro and in vivo [54][55][56]. Oxidative stress causes several types of pathological states including inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, among the lipid components of Spirulina lipids, GLA bonded to GLs may possibly be the main contributor reducing the excess fat accumulation in the liver induced by the HFHSD. Furthermore, several studies have reported that GLA exerts a potent anti-inflammatory activity both in vitro and in vivo [54][55][56]. Oxidative stress causes several types of pathological states including inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, glucose, sucrose, and fructose have pro-inflammatory actions and enhance the levels of tumor necrosis factor-α (TNF-α) [21]. It is noteworthy that TNF-α itself can cause EFA deficiency state [22] that further enhances TNF-α formation due to the absence of the negative regulation exerted by GLA, DGLA, AA, PGE1, lipoxins, resolvins, protectins, and maresins [23][24][25][26][27][28][29][30].…”
Section: Metabolism Of Essential Fatty Acids and Factors That Influenmentioning
confidence: 99%
“…However, a decrease in these acids’ levels may lead to the development of inflammatory diseases [ 24 , 27 ]. In addition, GLA suppresses inflammation mediators such as IL-1β, IL-6, and TNF-α cytokines [ 12 , 28 ]. In contrast, 15-HETrE acid, which is a product of the oxidation of dihomo-γ-linolenic acid by 15-LOX, has the ability to inhibit the synthesis of series 4 leukotrienes, whose elevated levels cause intensified pathological cell hyperproliferation [ 24 ].…”
Section: Biological Activity Of Evening Primrose Oil ( Omentioning
confidence: 99%